2022
DOI: 10.3389/fneur.2022.809843
|View full text |Cite
|
Sign up to set email alerts
|

Functional Remodeling Associated With Language Recovery After Repetitive Transcranial Magnetic Stimulation in Chronic Aphasic Stroke

Abstract: BackgroundRepetitive transcranial magnetic stimulation (rTMS) has shown promising efficacy in improving the language functions in poststroke aphasia. However, randomized controlled trials were lacking to investigate the rTMS-related neuroimaging changes underlying the therapeutic effects on language improvement in chronic aphasia.ObjectiveIn this study, we aimed to evaluate the effects of low-frequency rTMS (LF-rTMS) on chronic poststroke aphasia. We hypothesized that the deactivation of the right pars triangu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Our recent publication reported that right pars triangularis inhibition by LF‐rTMS may restore the interhemispheric inhibition imbalance and facilitate network remodeling [37]. The functional imaging findings suggested that the direct suppression of right pars triangularis decreased its functional connectivity with right pars opercularis, which is consistent with the findings of Naeser et al [29].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our recent publication reported that right pars triangularis inhibition by LF‐rTMS may restore the interhemispheric inhibition imbalance and facilitate network remodeling [37]. The functional imaging findings suggested that the direct suppression of right pars triangularis decreased its functional connectivity with right pars opercularis, which is consistent with the findings of Naeser et al [29].…”
Section: Discussionsupporting
confidence: 86%
“…Dynamic reorganization of the language network after a left frontal infarction involved bilateral frontal, temporoparietal and temporal areas (i.e., perilesional left and homologue right language areas) [1, 9]. Our previous functional magnetic resonance imaging (fMRI) study further found that inhibitory rTMS‐induced functional remodeling in left and right language networks was significantly correlated with language improvement [6]. In fact, aphasia is considered as a network disorder involving language reorganization within domain‐specific and domain‐general networks [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…The first four volumes of BOLD images were discarded from the subsequent analyses. Nuisance signals, including the six head movement parameters, the mean signal of cerebrospinal fluid, white matter, and global signal, were regressed out from the smoothed images, and low-frequency signals (0.01–0.1 Hz) were extracted using MATLAB software (2018b; Mathworks, Natick, MA) and an in-house scripts [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…We performed a stepwise multivariate regression analysis to investigate the relationship between the altered functional sensorimotor network and the primary outcome of FMA-UE improvement (T2–T1 and T3–T1 as the dependent variables) in the real tDCS group and the sham group, respectively, as previously described [ 47 ]. To avoid an overfitting model, only the altered FC (z scores with large Cohen’s f 2 > 0.5) estimated by simple linear regression for FMA-UE improvements were included in the multivariate regression model with adjustment for age and sex [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…The elucidation of the mechanisms of aphasia recovery in stroke is clinically important and essential for establishing effective neuro-rehabilitation strategies. More specifically, novel non-invasive brain stimulation therapies such as repetitive transcranial magnetic stimulation (rTMS) or transcranial direct current stimulation (tDCS) can be applied to specific neural structures which contribute to aphasia recovery [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%